Observations on the ontogeny of butterfish Stromateus stellatus larvae (Pisces: Stromateidae) off central Chile - Herrera, Guillermo A.; Zavala-Muñoz, Francisca; Landaeta, Mauricio F. (Revista de Biología Marina y Oceanografía, 2018)
Although larvae of the starry butterfish Stromateus stellatus (Family Stromateidae) are often observed in coastal waters of the southeastern Pacific Ocean, there is no formal description of the species’ early development. Using ichthyoplankton samples collected off central Chile, the larval development, including observations on osteology of late postflexion stage larvae, and temporal differences in larval densities in nearshore waters are described. Preflexion larvae have a short, rounded snout and a distinctive pigment pattern. Notable transformations throughout the development from early preflexion to postflexion are the increase in preanal length from less than 40 to more than 50% of body length (BL) and in body depth from 5 to 33% BL. Initially, larvae develop 3 melanophores on the dorsal contour of the body, small melanophores at the jaw angle, and a row along the ventral margin of the tail. Large melanophores dorsal and ventral to the gut, intestine, and above the swim bladder are also present in early preflexion. After notochord flexion, larvae develop light pigmentation on the sides of the tail, and heavy pigmentation on the head and trunk. The larvae share the general shape of the family, with a body that increases notably in depth and preanal length during development; they present characteristic pigmentation that differentiates them from larvae of related species. The larvae were recorded in low density (less than 6 ind. 100 m-3) in the nearshore during mid-spring (October) and early summer (late December until mid-January) off central Chile. The occurrence of the larvae in the plankton recorded in central Chile is consistent with information from literature of larval distribution and reproductive activity in adults.